Herbal medicinal products for respiratory infections in the pediatric population - Marčetić, Mirjana; Arsenijević, Jelena (Archives of Pharmacy, 2025)
Cough and cold represent some of the most prevalent indications for using herbal medicinal products in pediatric care across European countries. These herbal medicines are generally regarded as safe, with their efficacy predominantly classified as good to very good. Traditional herbal medicinal products based on mucilaginous herbal drugs like Althaeae radix, Malvae folium, Lichen islandicus and Plantaginis lanceolatae folium are used in the treatment of oral and pharyngeal inflammations and associated dry cough. For productive coughs, herbal medicinal products with well-established use, based on Hederae folium, or a range of traditional herbal medicinal products containing Primulae radix, Thymi herba, and other aromatic drugs and essential oils are administered. It is important to note that products containing essential oils and certain aromatic herbal drugs are contraindicated in children under 2 to 2.5 years of age due to the risk of laryngospasm. In the pediatric population, products derived from Matricariae flos, Pelargonii radix, Tiliae flos and Sambuci flos are used to relieve various cold symptoms. Use is restricted to children over a certain age, mostly due to lack of safety data, and in some cases due to the possibility of certain adverse effects.
Keywords: herbal drugs; cough and cold; children; demulcent; expectorant